Frequent intravenous pulses of growth hormone together with glutamine supplementation in prolonged critical illness after multiple trauma: effects on nitrogen balance, insulin resistance, and substrate oxidation - Duska, Frantisek; Fric, Michal; Waldauf, Petr; Pazout, Jaroslav; Andel, Michal; Mokrejs, Pavel; Tůma, Petr; Pachl, Jan (Critical care medicine, 2008)
OBJECTIVES: To estimate the efficacy and metabolic effects of growth hormone substitution as intravenous pulses together with alanyl-glutamine supplementation and tight blood glucose control in prolonged critical illness. DESIGN: Prospective double-blind, randomized trial with open-label control arm. SETTING: Intensive care unit of tertiary level hospital. PATIENTS: Thirty multiple trauma patients (median Injury Severity Score 34). INTERVENTIONS: Patients were randomized, at day 4 after trauma, to receive intravenous alanyl-glutamine supplementation (0.3 g/kg x day(-1) from day 4 until day 17) and intravenous growth hormone (administered days 7-17, full dose 50 microg/kg x day(-1) from day 10 onward) (group 1, n = 10) or alanyl-glutamine and placebo (group 2, n = 10). Group 3 (n = 10) received isocaloric isonitrogenous nutrition (proteins 1.5 g/kg x day(-1)) without alanyl-glutamine. MEASUREMENTS AND MAIN RESULTS: Cumulative nitrogen balance for the whole study period was -97 +/- 38 g of nitrogen for group 1, -193 +/- 50 g of nitrogen for group 2, and -198 +/- 77 g of nitrogen for group 3 (p < .001). This represents a daily saving of 300 g of lean body mass in group 1. Insulin-mediated glucose disposal, during euglycemic clamp, as a measure of insulin sensitivity, significantly worsened between days 4 and 17 in group 1 but improved in groups 2 and 3. Group 1 required significantly more insulin to control blood glucose, resulting in higher insulinemia (approximately 70 mIU in group 1 vs. approximately 25 mIU in groups 2 and 3). Despite this, growth hormone treatment caused an increase in plasma nonesterified fatty acid (approximately 0.5-0.6 mM in group 1 in comparison with approximately 0.2-0.3 mM in groups 2 and 3) but did not influence lipid oxidation. There were no differences in morbidity, mortality, or 6-month outcome among the groups. CONCLUSIONS: Treatment with frequent intravenous pulses of low-dose growth hormone together with alanyl-glutamine supplementation improves nitrogen economy in patients with prolonged critical illness after multiple trauma but worsens insulin sensitivity. Tight blood glucose control is possible but requires higher doses of insulin.
Keywords: Insulin Resistance; Middle Aged; pulzní dávkování léků; intravenózní infuze; energetický metabolismus; Critical Care; lidé středního věku; Prospective Studies; prospektivní studie; Adult; mužské pohlaví; Nitrogen; kombinovaná farmakoterapie; Survival Rate; Multiple Trauma; Length of Stay; dvojitá slepá metoda; lidský růstový hormon; Double-Blind Method; míra přežití; dospělí; Humans; délka pobytu; lidé; krevní glukóza; inzulinová rezistence; Blood Glucose; APACHE; polytrauma; Creatinine; Drug Therapy, Combination; Infusions, Intravenous; dipeptidy; Female; Body Mass Index; Calorimetry, Indirect; Ammonia; péče o pacienty v kritickém stavu; index tělesné hmotnosti; nepřímá kalorimetrie; ženské pohlaví; Energy Metabolism; Male; Dipeptides; kreatinin; Human Growth Hormone; amoniak; dusík; Pulse Therapy, Drug; pilotní projekty; Pilot Projects